2020
DOI: 10.1021/acssuschemeng.9b06663
|View full text |Cite
|
Sign up to set email alerts
|

Merger of Whole Cell Biocatalysis with Organocatalysis Upgrades Alcohol Feedstocks in a Mild, Aqueous, One-Pot Process

Abstract: Biosynthetic methods have the potential to deliver value-added chemicals from renewable feedstocks. However, despite major advances in metabolic engineering and synthetic biology, the rapid engineering of microbes to deliver high yields and titers of target compounds remains as a challenge. Here, we disclose a new chemical catalysis-based strategy for expanding the types of products available from unmodified microorganisms. By combining Gluconobacter oxidans as a whole cell biocatalyst in a single pot with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Starting e.g., from 1-butanol, 2-ethyl hexenal can be obtained representing an interesting approach to upgrade bio-based alcohols. Finally, a recently established combination of biocatalytic (ADH-or AlcOx-catalyzed) alcohol oxidation with organocatalytic (amino acid-catalyzed) aldol condensation is worth mentioning (Scheme 14) [129][130][131]. Starting e.g., from 1-butanol, 2-ethyl hexenal can be obtained representing an interesting approach to upgrade bio-based alcohols.…”
Section: Oxidation Of Primary Alcohols To Aldehydesmentioning
confidence: 99%
“…Starting e.g., from 1-butanol, 2-ethyl hexenal can be obtained representing an interesting approach to upgrade bio-based alcohols. Finally, a recently established combination of biocatalytic (ADH-or AlcOx-catalyzed) alcohol oxidation with organocatalytic (amino acid-catalyzed) aldol condensation is worth mentioning (Scheme 14) [129][130][131]. Starting e.g., from 1-butanol, 2-ethyl hexenal can be obtained representing an interesting approach to upgrade bio-based alcohols.…”
Section: Oxidation Of Primary Alcohols To Aldehydesmentioning
confidence: 99%
“…In a subsequent study, Stewart and co-workers showed that the aldehyde substrate could be produced via the oxidation of primary alcohols by wild-type Gluconobacter oxydans . 41 Coupling this with a lysine organocatalyst at 900 mol% provided the target α,β-unsaturated products in up to 88% yield over 24–48 h, redirecting metabolism away from further oxidation of the aldehyde to the carboxylic acid by native dehydrogenases. A range of cross-aldol products could also be obtained through addition of other C 2 –C 6 alcohol substrates ( Fig.…”
Section: Biocompatible Chemistry For Small Molecule Synthesismentioning
confidence: 99%
“…We recently expanded this system to show that organocatalysts can intercept microbial metabolites and redirect flux to industrially relevant compounds without the need to engineer the microorganism (Figure 8). [81] Aqueous solutions of n‐aliphatic alcohols were oxidized to their corresponding n‐aliphatic aldehydes with Gluconobacter oxydans whole cell biocatalysis. In the absence of lysine, which acts as an aldol catalyst, the aldehyde is further oxidized to the corresponding carboxylic acid.…”
Section: Combining Chemocatalysis With Living Cellsmentioning
confidence: 99%